Managing the psychological contract : employee relations in South Asia - Abdullah, ABM (Palgrave Macmillan, 2017)
This book explores the differences between Western and non-Western cultures to provide a more comprehensive understanding of psychological contract and its consequences on employees' behavioral, attitudinal, and cognitive outcomes. Further, it discusses the culturally-relevant elements of HR practices that affect employee expectations, job satisfaction, commitment, and motivation based on their perceptions of the level of fulfilment of their psychological contract. Integrating both qualitative and quantitative methods, it is the first book to examine the current state of the South Asian workforce and will advance research on industrial relations, employee relationship management, and corporate management of South Asian employees around the world.